Comparative reflections of Australian and African female academics on working from home during COVID-19 - Singh, Upasana G.; Watson, Rashmi; Nair, Chenicheri S. (Frontiers in Psychology, 2022)
The COVID-19 pandemic has taken a heavy toll on women globally, and female academics were no exception to the unprecedented, forced shift to working from home. Increased workloads, additional domestic responsibilities, and extended working hours have led to high levels of dissatisfaction among this group of academics. This disruption has also impacted mental and physical wellbeing. There has been limited research on the experiences of female academics during the transition to the new work environment in the early stages of the pandemic. This research compares the opportunities and challenges faced, as well as the support received, by female academics in Australia and Africa. Specifically, this study reports on the changing roles; demands of increased workloads; challenges, and opportunities faced both personally, and in general, an exploratory, qualitative approach was adopted in this study. An online questionnaire was developed and distributed through mailing lists in Africa and Australia; LinkedIn; as well as a personal invitation by the researchers on WhatsApp and email. Purposeful and snowballing sampling female academics in Australia and Africa were targeted, Inclusion criteria for this study were female academics employed at any higher education institution (HEI), private or public, in contract, and part-time and full-time employment in Australia and Africa since the start of the pandemic (February 2020). A total of 171 respondents (144 from Australia and 27 from Africa) were received from a larger, global study with 260 responses gathering data about female academics’ experiences during COVID-19. The data were analyzed using thematic and inductive analyses. The study sheds light on workload, motivation, perceptions about career progression, and work status. The research contributes to the body of knowledge of femaleacademic work, gender disparity, and higher education impact during COVID-19. The research aims to add value to the literature that supports the growing feminism in academia to ensure HEIs support this cohort of academics.